2015
DOI: 10.2459/jcm.0b013e328364be3c
|View full text |Cite
|
Sign up to set email alerts
|

Higher BMI in heart failure patients is associated with longer survival only in the absence of diabetes

Abstract: The reported obesity paradox in heart failure can only be observed in nondiabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
3
14
1
Order By: Relevance
“…We now reach a similar conclusion, albeit with a larger patient cohort and longer follow‐up, but using similar definitions of diabetes. One point of departure between our study and that of Pinho et al . is our more extensive categorization of BMI, as opposed to the split of either above or below 25 kg/m 2 (i.e.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations
“…We now reach a similar conclusion, albeit with a larger patient cohort and longer follow‐up, but using similar definitions of diabetes. One point of departure between our study and that of Pinho et al . is our more extensive categorization of BMI, as opposed to the split of either above or below 25 kg/m 2 (i.e.…”
Section: Discussioncontrasting
confidence: 86%
“…The authors found that once HF was established, overweight and obese patients fared better than normal weight patients, but this was irrespective of diabetes status. More recently, Pinho et al . evaluated BMI and diabetes in 503 ambulatory HF patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In hemodialysis patients with increasing body mass index (BMI), the survival rate improves [ 1 , 2 ]. This phenomenon has also been observed in patients with heart failure, obstructive lung disease, cancer and in elderly people [ 3 , 4 ]. This survival paradox can be explained by the fact that an excess of fat mass is protective in the short term, though is likely to be harmful over a longer period of time.…”
Section: Introductionmentioning
confidence: 74%